2001
DOI: 10.1086/319758
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Pregnant Women

Abstract: Brucella species occasionally cause spontaneous human abortion, but theories regarding whether they do so more frequently than do other infectious pathogens remain controversial. We reviewed 92 pregnant women who presented with acute brucellosis at a Saudi Arabian hospital. From 1983 through 1995, the cumulative incidence of pregnancy and brucellosis was 1.3 cases per 1000 delivered obstetrical discharges. The incidence of spontaneous abortion in the first and second trimesters was 43%, and the incidence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
4
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 19 publications
8
154
4
5
Order By: Relevance
“…Our current study shows a statistically significant difference in the incidence of abortion and the incidence of IUFD but not the incidence of preterm labour between pregnant women with positive brucellosis antibodies and control pregnant women. This is consistent with Malone et al (36), Makhseed et al (37) and Khan et al [35]; however, these results are contrary to the study of Seoud et al [17] who stated that Brucella infection has a lesser role in human abortion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our current study shows a statistically significant difference in the incidence of abortion and the incidence of IUFD but not the incidence of preterm labour between pregnant women with positive brucellosis antibodies and control pregnant women. This is consistent with Malone et al (36), Makhseed et al (37) and Khan et al [35]; however, these results are contrary to the study of Seoud et al [17] who stated that Brucella infection has a lesser role in human abortion.…”
Section: Discussionsupporting
confidence: 88%
“…This result exceeds the 10% rate reported by Crisculo and di Carlo [29] and that of Sarram et al [32] who observed that among 51 pregnant women infected with brucellosis the incidence rate of abortion was only 11.6 %. Contrarily, the incidence rate of abortion in our study is less than that reported in other studies (Madkour et [33][34][35].…”
Section: Discussioncontrasting
confidence: 84%
“…Antimicrobial treatment at this point is extremely important for maternal and baby's health (27,28). Doxycycline and streptomycin are not recommended during pregnancy because of their teratogenicity.…”
Section: Brucellosis In Pregnancymentioning
confidence: 99%
“…Symptoms of the acute phase of human brucellosis are flu-like periodic fevers with muscle and joint pain followed by lymphadenopathy, hepatosplenomegaly, and development of granulomas at multiple sites of the body (Franco et al 2007a). Common complications, some of which are fatal if not promptly diagnosed and treated, are arthritis, liver abscess formation, neurobrucellosis, endocarditis, and even abortion in the endemic regions (Khan et al 2001;Young 2005;Franco et al 2007b). …”
Section: Bartonella and Brucella: Closely Related Pathogens With Distmentioning
confidence: 99%